2017
DOI: 10.4103/ijri.ijri_30_17
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided radiofrequency ablation in osteoid osteoma: Result from a tertiary cancer centre in India

Abstract: Aims:The aim of this study is to evaluate the clinical efficacy of computed tomography (CT)-guided radiofrequency (RF) ablation as a minimally invasive therapy for osteoid osteoma.Materials and Methods:This is a retrospective analysis of prospectively maintained data of 43 symptomatic osteoid osteoma patients who were treated by radiofrequency ablation (RFA). Forty out of 43 patients were naive cases and underwent primary treatment for osteoid osteoma with RFA, whereas 3 patients included in the study underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
2
5
0
1
Order By: Relevance
“…This could explain why many patients reported a long course of disease at their first survey, with up to 8-month period of continuing pain before having a correct diagnosis. Similar observations have already been proposed [ 18 , 24 ]. Our results clearly correlate the pain suffered by patients affected by OO with age, lesion size at baseline and lesion location (atypical site > typical site): elderly patients and patients with bigger and/or atypically located OO complained of stronger pain.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This could explain why many patients reported a long course of disease at their first survey, with up to 8-month period of continuing pain before having a correct diagnosis. Similar observations have already been proposed [ 18 , 24 ]. Our results clearly correlate the pain suffered by patients affected by OO with age, lesion size at baseline and lesion location (atypical site > typical site): elderly patients and patients with bigger and/or atypically located OO complained of stronger pain.…”
Section: Discussionsupporting
confidence: 90%
“…Our technical and clinical success were comparable to those assessed in previous published studies, ranging from 91–95% [ 3 , 12 , 18 , 19 ]. In particular, Kulkarni et al [ 18 ] recorded a technical success rate of 100%, with a primary and secondary clinical success rate of 97.7%, and 100%, respectively. Rehnitz et al [ 19 ] reported primary and secondary success rates of 96.1% and 100%, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…RFA of OOs has been extensively reported in the past[19202122] with success rates approaching 100%. The key to successful treatment of OOs is complete removal or destruction of the tumor nidus.…”
Section: Discussionmentioning
confidence: 99%